The Differential Estimation of Let-7b and miRNA-96 in the Serum and the Tissue Samples Obtained from Chemically Induced Oral Carcinogenesis in Rats - Maher, Rojin Jameel; Raziq, Amir Hani; Raziq, Alaa Hani (Iraqi Journal of Science, 2024)
Let-7b and miRNA-96 are among the dysregulated microRNAs in various diseases. Selected seventy-five male rats were divided into five equal treatment groups and were given 4-nitroquinoline 1-oxide (4-NQO) by drinking water (50 ppm) for five different drenching periods. To each treatment group, a control group of five males was also assigned. The oral pathological changes were microscopically evaluated thereafter. Histopathological changes indicating dysplasia or frank carcinoma were observed in the fifth treatment group only. Let-7b and miRNA-96 expressions in the tongue tissue and serum were quantified using quantitative reverse transcription PCR (qRT-PCR). The fifth treatment group only showed signs of severe and well differentiated squamous cell carcinoma in percentages of 40% and 26.7%, respectively. Let-7b expression appeared to be statistically non-significantly different when up and downregulation were compared in tissue and serum samples (p=.3; p=.08). For miRNA-96, it seemed that no statistically significant difference (p=.08) was attained when tissue samples were studied, while the difference was statistically significant (p=.04) when serum samples were considered. Let-7b can be considered a good biomarker for oral squamous cell carcinoma (OSCC) in tissue and body fluid as well, while miRNA-96 demonstrated a controversial result as far as the tissue type was considered and, thus, can play the role of an oncogene (OG) or a tumor suppressor gene (TS).